Malala : my story of standing up for girls' rights - Yousafzai, Malala, 1997-; McCormick, Patricia, 1956-; Robbins, Sarah J. (Little, Brown and Company, 2018)
"Malala retells her story of speaking out for girls' education rights for chapter book readers"--